EDUCATED UNEMPLOYMENT IN AFRICA: DIRECTIONS OF RESEARCH - Teshome, Mulat (The Ethiopian Journal of Education, 2024)
Reports coming out of Africa In recent years indicate a trend of worsening unemployment for leavers of the schooling system. This short article surveys the state of current research 011 the subject of educated unemployment in the continent. While attempts are made to cover the wide variations in reported writings, the survey makes a determined focusing 011 what may be termed as "economic" research. The conclusion drawn is that little else is done beyond The application of theories and generalizations already developed to describe and analyse the phenomena in Western countries. Attempt is also made to highlight a proposition already raised in The text by means of Sudanese data.